Allyl isothiocyanate baited traps to monitor cabbage flea beetles (Phyllotretra spp., Coleoptera: Chrysomelidae) - Benedek, P.; Bakcsa, F.; Tóth, M.; Csonka, E. (International Journal of Horticultural Science, 2005)
A new trapping concept has been proposed based on a volatile compound, allyl isothyocianate, known to be attractant to some of these insects for a long time. (l) The first question was whether this compound is effectively attractive to all flea beetle species attacking cabbage under our conditions? Field experiments were made at different localities with non-sticky baited traps early and late spring. Eleven Phyllotreta species attacking cabbages were captured at baited traps most of them were first observed at this bait. So the bait has proved to be sufficient for use for trapping purposes effectively. • Based on these findings a second question arose whether the captured samples reflected the specific composition of natural flea beetle populations at trapping localities? To reply the question field samples were taken at four different kinds of cabbage crops and at a fallow ground in the close vicinity by a manual sampler device suitable to detect the local composition of flea beetles and trapping was made parallel with baited and unbaited traps from early spring to early autumn. No significant differences were found between the specific structures of Phyllotreta assemblages sampled with the different methods applied. This means baited traps reflected the specific composition of local Phyllotreta populations fairly well. • Thirdly, the most effective trap design was searched for. Some sticky and non-sticky trap designs which had been developed to capture other insects were compared. The tested sticky and funnel trap designs baited with allyl isothiocyanate captured large numbers of flea beetles attacking cabbages. Results showed that non-sticky funnel traps were more effective than sticky delta traps. Accordingly, non-sticky funnel trap designs can advantageously be used and could possibly be recommended in plant protection practice to monitor flea beetles attacking cabbages as their catching capacity is considerably greater than that of the delta type and additionally captured beetles are much cleaner, more intact and consequently their identification is much easier.